Pengaruh Self-Compassion terhadap Korban Bullying Pada Siswa SMA Negeri 14 Semarang - Saputri, Nurshafilla Rizka; Rakhmawati, Dini; Mustianah, Mustianah (IKIP Siliwangi, 2024)
The aim of this research was to determine the effect of self-compassion on bullying victims among students at SMA Negeri 14 Semarang. This research uses a quantitative ex post facto design approach. The population in this study was 287 students. The research sample consisted of 287 class X students taken using probability sampling techniques. The data collection tools used were the self-compassion scale and the bullying victim scale. The validity test results of the self-compassion scale are in the range 0.176 – 0.776 and the bullying victim scale is in the range 0.170 – 0.760. The reliability test results of the self-compassion scale had a Cronbach's alpha value of 0.944 and the bullying victim scale had a Cronbach's alpha value of 0.909, both of which were included in the strong category. Based on these results, both scales can be said to be valid and reliable. This research uses multiple regression testing techniques as a data analysis technique. The self-compassion variable is in the medium category (M = 81,25; SD = 9,10) and the bullying victim variable is in the medium category (M = 100,33; SD = 9,51). The results of this study show that self-compassion has an effect on victims of bullying among students at SMA Negeri 14 Semarang. Self-compassion explains that it has an influence of 33,6% (R2 =.336). The results of this research have implications for guidance and counseling in carrying out prevention and alleviation functions for students who are victims of bullying and have traumatic impacts from acts of bullying behavior at school.